Effect of Aureobasidium pullulans strains against Botrytis cinerea on kiwifruit during storage and on fruit nutritional composition. (June 2018) - Di Francesco, A.; Mari, M.; Ugolini, L.; Baraldi, E.
Abstract: Kiwifruit, wounded at the equator or by pedicel removal, to simulate the stem end wound, were treated with Aureobasidium pullulans (L1 and L8 strains) and subsequently inoculated with conidia of Botrytis cinerea . Fruits were stored at -1 °C in normal refrigeration (NR) or in controlled atmosphere (CA) (2% O2 ; 4.5% CO2 ). After 4 months, both antagonists significantly reduced the disease in all experiments, L1 better than L8. In NR, their efficacy was higher than 80%. In CA, the disease reduction was lower: between 30% (L1) and 60% (L8). The ability of both strains to compete with the pathogen for nutrients was tested in kiwifruit juice (0.5%) by in vitro experiments. Antagonists significantly reduced pathogen conidia germination in water and in juice. An HPLC analysis was performed to define the amino acid composition of kiwifruit juice upon L1 and L8 treatment. L1 and L8 greatly increased the concentration of both glutamic and aspartic acids and stimulated the production of new amino acids, although at low concentrations. Each amino acid displayed an antifungal effect against mycelium growth of B. cinerea. Finally, L1 and L8, cold tolerant and active strains in CA, can be effectively applied to control the stem end rot of kiwifruit in long storage. Highlights: After 4 months of storage A. pullulans strains reduced kiwifruit gray mold disease. A. pullulans strains increased in kiwifruit juice amino acids concentration. Aspartic and glutamic acids displayed an antifungal effect against B. cinerea .